Quelle présence pour accompagner l'apprentissage à distance ? - Nathalie Carminatti; Christiana Charalampopoulou; Marie-France Carnus (Université de Provence, 2022)
Due to the pandemic, teachers and trainers from kindergarten to university have had to switch from "face-to-face" teaching to remote or hybrid practices, alternating synchronous and asynchronous moments, in order to ensure the prescribed "pedagogical continuity". This forced change has generated redefinitions of times and spaces of teaching and learning leading to new support practices. In the context of two examples of Hybrid Clinical Didactics Cooperative Engineering, we question the concept of presence and the different forms that remote presence can take in order to support learning in synchronous and asynchronous phases of remote teaching and learning situations. The two case studies reveal support practices in synchronous as well as in ante, post and inter-synchronous modes.